Miniaturized Force-Torque Sensor Built in a Robot End-Effector for Delicate Tool-Tip Gripping Control - Kim, Yoon-Gu; Kwak, Jeong-Hwan; Hong, Dae-Han; An, Jinung (Elektronika ir Elektrotechnika, 2014)
A robot end-effector or gripper must have the capability to endure both the weight and acceleration of the object in spite of its frequent movement while a robot uses the gripper to handle various objects and assists the tasks of a person. In this regard, it is essential to directly measure the amounts of gripping force and torque applied to the object by the gripper. This work presents the design and development of a miniaturized force-torque (FT) sensor built inside the gripper with a thickness similar to that of the human finger. It enables efficient use of the FT sensor for delicate tool-tip gripping control of the gripper in the packaging line of electrical devices such as mobile phones. The FT sensor is optimized for acquiring the 3-DoF force-torque information of a single-axis gripping tool. The performance of the FT sensor has been verified through characterization experiments and integrated tests on the gripper. DOI: http://dx.doi.org/10.5755/j01.eee.20.6.7258